2016
DOI: 10.1186/s12884-016-1136-0
|View full text |Cite
|
Sign up to set email alerts
|

Breech delivery at a University Hospital in Tanzania

Abstract: BackgroundThere is a global increase in rates of Cesarean delivery (CD). A minor factor in this increase is a shift towards CD for breech presentation. The aim of this study was to analyze breech births by mode of delivery and investigate short-term fetal and maternal outcomes in a low-income setting.MethodsThe study design was cross-sectional and the setting was Muhimbili National Hospital (MNH), Dar-es-Salaam, Tanzania. Subjects were drawn from a clinical database (1999–2010) using the following inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Multiple authors have suggested that planned cesarean delivery may not be the best option in low‐income countries . Limited retrospective studies of mode of delivery in breech presentation in low‐income countries in sub‐Saharan Africa, primarily conducted at urban referral hospitals, have had conflicting results, but the majority of the studies demonstrate an increased perinatal risk with vaginal delivery . However, the rate of cesarean delivery for malpresentation at African study sites in the Global Network, which represent primarily non‐urban, non‐referral healthcare facilities, was low and increased only modestly over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple authors have suggested that planned cesarean delivery may not be the best option in low‐income countries . Limited retrospective studies of mode of delivery in breech presentation in low‐income countries in sub‐Saharan Africa, primarily conducted at urban referral hospitals, have had conflicting results, but the majority of the studies demonstrate an increased perinatal risk with vaginal delivery . However, the rate of cesarean delivery for malpresentation at African study sites in the Global Network, which represent primarily non‐urban, non‐referral healthcare facilities, was low and increased only modestly over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that vaginal breech deliveries are associated with adverse fetal outcomes. 1,5,6 There were no major maternal complications.…”
Section: Discussionmentioning
confidence: 89%
“…In two studies in Sub-Saharan countries, there was a strong association between vaginal breech delivery of singleton term pregnancies and maternofetal morbidity, with newborns more likely to suffer from birth asphyxia. 5,6 In a Saudi Arabian study, there was higher neonatal mortality found in vaginal breech delivery for singleton preterm breech fetus. 7 Vaginal breech delivery is still a safe option without compromising maternal and neonatal outcome if strict criteria are met before and during labour.…”
Section: Introductionmentioning
confidence: 99%
“…The increased likelihood of cesarean delivery among nulliparous breech term pregnancies (Robson group 6) after CBA, was associated with an increase in the relative size of the respective group. This was because cesarean delivery was mandatory based on the local and international evidence of severe perinatal morbidity associated with vaginal breech delivery; and also there was lack of accessible clinical guidelines for safe breech delivery at MNH. Nonetheless, training care providers on external cephalic version (ECV) promotes its use and reduces unnecessary primary cesarean delivery .…”
Section: Discussionmentioning
confidence: 99%
“…The increased likelihood of cesarean delivery among nulliparous breech term pregnancies (Robson group 6) after CBA, was associated with an increase in the relative size of the respective group. This was because cesarean delivery was mandatory based on the local 16 and skin-to-skin (Kangaroo) mother care. 20 However, preterm pregnancies received at MNH tend to include cases with other complications such as premature rupture of membranes, antepartum hemorrhage, pre-eclampsia, or eclampsia; hence, there is an increased likelihood of preterm cesarean delivery and adverse perinatal outcomes.…”
Section: Discussionmentioning
confidence: 99%